Algebraic groups and number theory, Volume I - Platonov, Vladimir P. 1939-; Rapinčuk, Andrej S. 1960-; Rapinchuk, Igor (Cambridge University Press, 2023)
This is the first volume of a two-volume book that offers an in-depth, and essentially self-contained, treatment of the arithmetic theory of algebraic groups. It is accessible to graduate students and researchers in number theory, algebraic geometry, and related areas.
"The translation of the first Russian edition was prepared by Rachel Rowen."
Keywords: Algebraic number theory; Linear algebraic groups